Imperial Moth Eacles imperialis imperialis (Drury, 1773) (Insecta: Lepidoptera: Saturniidae: Ceratocampinae) - Donald W. Hall (EDIS, 2014)
The imperial moth is one of our largest and most beautiful moths. It is also the most variable in appearance and the most widely distributed of our large eastern U.S. saturniid moths. This 9-page fact sheet was written by Donald W. Hall, and published by the UF Department of Entomology and Nematology, September 2014. (Photo: Donald W. Hall, University of Florida)